L’accounting standard overload: “l’hangman’s noose” delle small business anglosassoni - Sorrentino, Marco (Piccola Impresa / Small Business, 2013)
Anglo-Saxon accounting literature has traditionally connected the sharp and unexpected decline in the U.S. stock market in the 70’s and the following proliferation of accounting standards with the origin of a complex problem for small business entities, defined accounting standards overload. The interest for this phenomenon has quickly spread from the U.S. to the other Anglo-Saxon countries with a series of official pronouncements and not a few theoretical and/or empirical researches, trying to get a possible solution to this specific problem. As a result, this paper analyzes the main literature (par. 2) and the development (par. 3) of the general phenomenon of accounting standard overload and describes the solution adopted in the main Anglo-Saxon countries (par. 4); finally the author shares his personal observations (par. 5).